Patient characteristics of women with obstetric fistula from western Nepal - Berger, Salome (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To assess the social, demographic and reproductive health characteristics of women with obstetric fistula from western Nepal who attended fistula camps in Surkhet between 2012 and 2017. To investigate factors associated with attendance of at least one antenatal care session (ANC). Methodology: This was a retrospective study of 125 medical records. Baseline social, demographic and reproductive health characteristics were summarized. Associations between baseline characteristics and attendance to at least one ANC session were analyzed using statistical tests and multivariable logistic regression. Results: The mean age at presentation was 41.4 years (SD=12.4) and duration of history of OF was 15.4 years (SD=11.4), which were both higher than in other studies. Education was associated with higher uptake of ANC and delivery at a health facility was also associated with having visited at least one ANC session. Conclusions: The characteristics of women attending this camp are, for the most part, similar to those of OF patients in previous studies. The long duration of history of OF in Nepal calls for more effective case-finding strategies. To improve ANC uptake and increase deliveries at health facilities, education was found to be a key factor.